Intention to Book Open Trip Packages Among Novice Travelers: A Trust-Based Approach in Tourism Context - Suryana, Marceilla; Susanto, Eko (Journal of Tourism Sustainability, 2025)
This study investigates the factors influencing the intention of novice travelers to book open trip packages by proposing and testing a trust-based model within a digital tourism context. Drawing on the Technology Acceptance Model (TAM), consumer trust theory, and destination image theory, the research integrates seven key constructs: ease of access to travel platforms, functional benefits, perceived travel risks, digital travel reviews, destination attractiveness, trust in tour operators, and booking intention. Data were collected from 291 Indonesian respondents using a structured online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that trust in tour operators significantly mediates the relationship between functional, technological, and experiential antecedents and booking intention. Destination attractiveness, functional benefits, and digital travel reviews emerged as strong predictors of trust, while perceived travel risks showed a marginal effect. Additionally, ease of access plays a dual role in enhancing functional perceptions and destination appeal. The study contributes to tourism theory by contextualizing digital trust mechanisms for novice users and offers practical guidance for tour operators and travel platforms in designing user-centered trust-building strategies.